ORNAO’96 Keynote Address Positioning Nursing Within a Reformed Health Care System - MacMillan, Kathleen (Operating Room Nurses Association of Canada Journal, 1996)
This article will discuss the many changes in the Ontario health care system and the role that nurses can play in making the change effective, in ensuring that stated goals are met and that the health of the citizens of Ontario is improved and not compromised during the change process.